2015
DOI: 10.1007/s11136-014-0903-5
|View full text |Cite
|
Sign up to set email alerts
|

Training clinicians in how to use patient-reported outcome measures in routine clinical practice

Abstract: Patient-reported outcome measures (PROs) were originally developed for comparing groups of people in clinical trials and population studies, and the results were used to support treatment recommendations or inform health policy, but there was not direct benefit for the participants providing PROs data. However, as the experience in using those measures increased, it became obvious the clinical value in using individual patient PROs profiles in daily practice to identify/monitor symptoms, evaluate treatment out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
151
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(162 citation statements)
references
References 32 publications
3
151
1
2
Order By: Relevance
“…lack of a control group, we are unable to conclude whether the moderate feasibility we found refers to PRO measurement in general or specifically to electronic PRO measurement. Moreover, our physicians were not adequately trained in the use of PROs, whereas this was previously identified as critical for the implementation of a PRO intervention [7,26,27]. Our study does not answer the question whether physicians actually use PRO results, and if so, how.…”
Section: Discussionmentioning
confidence: 86%
“…lack of a control group, we are unable to conclude whether the moderate feasibility we found refers to PRO measurement in general or specifically to electronic PRO measurement. Moreover, our physicians were not adequately trained in the use of PROs, whereas this was previously identified as critical for the implementation of a PRO intervention [7,26,27]. Our study does not answer the question whether physicians actually use PRO results, and if so, how.…”
Section: Discussionmentioning
confidence: 86%
“…Aligning the assessment content with the clinical purpose (e.g., screening versus monitoring a primary outcome of care) [23,25] and making PRO results more interpretable and actionable [26][27][28][29] have been recommended. Clinician training programs have also been successful in improving interpretation and use of PRO results [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, research showed that ROM feedback reports were often not used by therapists [11,66,82]. So, more attention may be needed for recurrent training of therapists on the use of ROM as an opportunity to discuss treatment progress, stagnation, or decline with the patient and to set common treatment goals together [4, 79,83]. Moreover, ROM results could be integrated in the treatment plan of a patient [25].…”
Section: Clinical and Research Recommendations For Use Of Rom In Treamentioning
confidence: 99%